Accounting Analisis Perbandingan Rasio Profitabilitas Menggunakan Net Profit Margin Dan Return On Equity Pada Sub Sektor Rokok Yang Listing Di Bursa Efek Indonesia - Dewi Sartika; Alwi; Alia Pratiwi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
This study aims to determine the comparative analysis of profitability ratios using net profit margin and return on equity in the cigarette sub-sector listed on the Indonesian stock exchange in 2014 to 2021. The method used in this study is the comparative analysis method. The population used in this study is the financial report of PT. Gudang Garam Tbk and Pt. Hm Sampoerna Tbk in the form of profit and loss statement data and an audited balance sheet in the form of a report on net income, sales and capital of PT. Gudang Garam Tbk from 1990 to 2021 which is for 31 years and Pt. Hm Sampoerna Tbk from 1990 to 2021, which is for 31 years. The financial statements were analyzed using profitability ratios to determine the performance of each cigarette industry. The ratio used is NPM AND ROE. The sampling technique used is purposive sampling, where the number of samples is obtained for 8 years (2014-2021). The data used are secondary data sourced from the financial reports of PT. Gudang Garam Tbk and Pt. Hm Sampoerna Tbk which is listed on the Indonesia Stock Exchange (IDX). The data analysis technique used is the Independent Test Sample T test or two-average difference test is used to test the two averages of two independent data groups and test the hypothesis using the t-statistical test using the SPSS 16.0 test. The results of the study show that there are differences in Net Profit Margin (NPM) and return on equity (ROE) at PT. Gudang Garam, Tbk with PT. HM Sampoerna, tbk.